Percentage of Carcass and Internal Organs of Japanese Quail After Given Organic Feed - Basri, Hasan; Sulastri, Meilinda Pahriana (Biogenesis: Jurnal Ilmiah Biologi, 2019)
Japanese quail (Coturnix coturnix japonica) is one of the livestock sectors that is efficient in providing nutrition, both from eggs and meat. This study aims to examine the effect of the provision of standard organic feed and organic feed containing cassava leaves, turmeric powder and ginger on increasing the percentage of carcasses and internal organs Japanese quail. This study used an experimental method with a completely randomized design pattern. The test animals used were 30 females Japanese quail which were divided into 3 groups, i.e. P0: control (given commercial feed); P1: given standard organic feed (corn, soybeans, bran and fish meal); P2: given organic feed (corn, soybeans, bran, fish meal, cassava leaves, turmeric, and ginger powder). Each group was treated with 5 replications. Data obtained were analyzed using analysis of variance (ANOVA) and continued with Duncan test with a confidence of 95% (P>0.05). The results showed that the provision of organic feed could not increase the percentage of carcass, heart, and liver, but could increase the percentage of Japanese quail gizzard.